ANALISIS PENGARUH KEMUDAHAN TRANSAKSI, HARGA, FASILITAS DAN KETEPATAN WAKTU TERHADAP KEPUASAN PELANGGAN KRL SOLO-YOGYAKARTA - Ivan Setyo Wibowo (Juremi: Jurnal Riset Ekonomi, 2023)
Transportation becomes a human need in carrying out every activity. KRL is one of the modes of transportation that is currently favored by the public to support their daily activities. This research research aims to determine how much influence the ease of transaction, price, facilities and timeliness have on KRL customer satisfaction. The quantitative type method was used in this study, the number of respondents used was 115. The technical analysis data used were multiple linear regression analysis and using the SPSS 21 tool. The results obtained in this study were the ease of transaction and price variables having a positive influence but not significant and variable facilities and timeliness have a positive effect on customer satisfaction. Taken together, the variables of ease of transaction, price, facilities and timeliness have a significant effect on KRL Solo- Yogya customer satisfaction.